Utility of lung ultrasound in childhood pneumonia in a tertiary care center - Shetty, Niharika; Sabapathy, Sarala; K., Mallesh (International Journal of Contemporary Pediatrics, 2020)
Background: Pneumonia is a major cause of childhood mortality and morbidity worldwide. Chest radiography has been used as a modality for diagnosing but has the disadvantage of radiation exposure and inter-observer variability. Hence studies have explored the possibility of using lung ultrasound in the diagnosis of pneumonia. To assess lung ultrasound (LUS) findings in childhood pneumonia and to correlate lung ultrasound findings with clinical findings. Methods: 210 children between 2 months to 5 years admitted in the hospital with diagnosis of pneumonia were enrolled in the study. They underwent LUS within 24 hours of admission and the results were analysed. Results: Out of the 210 patients enrolled in the study, 41 (19.5%) had positive LUS findings. However, LUS findings correlated well with clinical findings in cases with very severe pneumonia. Conclusions: This study showed that lung ultrasound cannot be used a sole diagnostic tool in childhood pneumonia, but it has a valuable role in detection of complications. Lung ultrasound will require more training for detection of early indicators of pneumonia.